Valences of the Dialectic: Un-Inheriting the Religion-Secular Binary in Sikh Studies and Beyond - Mandair, Arvind-Pal S. (Religions of South Asia, 2012)
This is a response by the author Arvind-Pal S. Mandair to the contributors of the Review Forum discussing his work Religion and the Specter of the West: Sikhism, India, Postcoloniality, and the Politics of Translation (hereafter RSW), published in 2009 by Columbia University Press.